2023
DOI: 10.1002/lpor.202200733
|View full text |Cite
|
Sign up to set email alerts
|

2D Transition Metal Carbides (MXenes) for Third Order Nonlinear Optics: Status and Prospects

Abstract: The family of 2D transition metal carbides, nitrides, and carbonitrides (MXenes) has attracted an enormous amount of attention due to their tunable optical, electronic, electrochemical, and mechanical properties. Recently, a new branch of MXenes materials research has emerged that is exploring and engineering the intrinsic optical response of MXenes, resulting in compact nonlinear optical (NLO) devices. As a novel 2D materials system, MXenes not only exhibit common advantages of classical 2D materials for NLO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 240 publications
0
9
0
Order By: Relevance
“…23 To date, more than 40 MXenes have been discovered and studied. As a novel 2D layered material, its unique electronic, chemical and optical properties make it potentially valuable for applications in biomedicine, 24 catalysis, 25,26 sensing, 27,28 energy storage, 29,30 nonlinear optics [31][32][33] and other fields. MXenes are obtained by etching layer A from the MAX phase, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…23 To date, more than 40 MXenes have been discovered and studied. As a novel 2D layered material, its unique electronic, chemical and optical properties make it potentially valuable for applications in biomedicine, 24 catalysis, 25,26 sensing, 27,28 energy storage, 29,30 nonlinear optics [31][32][33] and other fields. MXenes are obtained by etching layer A from the MAX phase, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In the past decade, low‐dimensional materials, such as CNTs, graphene, transition metal dichalcogenides (TMDCs), black phosphorus (BP), MXenes, and even organic nanomaterials have been widely employed as saturable absorption materials in laser mode‐locking due to their wide band response and ease of van der Waals integration. [ 13–25 ] It is worth noting that the pulse laser performances, including the damage threshold, long‐term stability, and mode‐lock start‐up threshold, are related to the coupling between the fiber optic medium and low‐dimensional materials, which is largely determined by the cleanliness of the interface. [ 14,26–28 ] However, traditional preparation and integration processes, such as solution‐based growth, drop cast, or polymer‐assistant transfer, inevitably introduce chemical residues or defects.…”
Section: Introductionmentioning
confidence: 99%
“…To date, the mode-locked lasers are achieved by using various SAs, including but not limited to semiconductor saturable absorber mirrors (SESAMs), black phosphorus (BP), carbon nanotubes (CNTs), transition metal dichalcogenides (TMDs), topology insulators (TIs), MXenes and MAX-phases [21][22][23][24][25][26][27][28][29]. For instance, Wang et al [30] have demonstrated the generation of mode-locked laser and dynamics of soliton at 1.5 μm using a VSe 2 /GO-based saturable absorber.…”
Section: Introductionmentioning
confidence: 99%